Search for anomalous $WW$ and $WWZ$ couplings with polarized $e$-beam at the LHeC - Cakir, I. T.; Cakir, O.; Senol, A.; Tasci, A. T. (arXiv, 2014)
We examine the potential of the $ep\to_{e}qX$ and $ep\to_{e}qZX$ processes to search for the anomalous couplings of $WW$ and $WWZ$ vertices at the LHeC with the electron beam energy of $E_{e}=60$ GeV and $E_{e}=140$ GeV. The difference of maximum and minimum bounds on the anomalous couplings, ($_$, $_$) and ($_{Z}$, $_{Z}$) are obtained as ($0.990$, $0.122$) and ($0.362$, $0.012$) without electron beam polarization at the beam energy of $E_{e}=140$ GeV for an integrated luminosity of $L_{int}=100$ fb$^{-1}$, respectively. With the possibility of $e-$beam polarization, we obtain more improved results as ($0.975$, $0.118$) and ($0.285$, $0.009$) for ($_, _$) and ($_{Z}, _{Z}$), respectively. The results are found to be comparable with the current experimental limits obtained from two-parameter analysis at the lepton and hadron colliders. It is found that the limits on the anomalous couplings ($_{Z}$, $_{Z}$) through the process $ep\to_{e}qZX$ at the LHeC can further improve the current experimental limits.

18 pages, 22 figures, 6 tables
Keywords: High Energy Physics - Phenomenology (hep-ph); FOS: Physical sciences; 7. Clean energy